Time Binning Method for Nonpulsed Sources Characterization With a Superconducting Photon Number Resolving Detector - Pasquale Ercolano; Ciro Bruscino; Daniela Salvoni; Chengjun Zhang; Mikkel Ejrnaes; Jia Huang; Hao Li; Lixing You; Loredana Parlato; Giovanni Piero Pepe (IEEE Transactions on Quantum Engineering, 2023)
Photon number resolving detectors find space in many fields, such as quantum optics, boson sampling, and fluorescence spectroscopy. In particular, the reconstruction of the input photon distribution is essential in quantum communications to detect photon-number-splitting attacks. In this work, we discuss the operation configurations of a photon number resolving detector based on superconducting nanostrips at a wavelength of 1550 nm from a temporal point of view. We set a time binning and acquired the number of recorded pulses per bin by means of a time-to-digital converter. We studied the predictions of two theoretical models and compared them to the experimental data in order to analyze their operation regimes depending on the binwidth and to employ them for the reconstruction of the input photon distribution. We applied this method to a continuous-wave laser source, showing that the former can be used for the characterization of nonpulsed light sources, even with a photon emission rate so low that the dark count rate of a superconducting nanostrip is not negligible.